1976
DOI: 10.1111/j.1365-2990.1976.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO CHARACTERISTICS OF A FOURTH VENTRICLE EPENDYMOMA MAINTAINED IN ORGAN CULTURE SYSTEMS: LIGHT AND ELECTRON MICROSCOPY OBSERVATIONS

Abstract: 1976) Neuropathology and Applied Neurobiology 2, 349-364 I n ritro characteristics of a fourth ventricle ependymoma maintained in organ culture systems : light and electron microscopy observationsExplants of a well-differentiated fourth ventricle ependymoma were grown on collagen-coated coverslips and in organ culture systems using gelatin sponge foam matrices and Millipore filter platforms. Viable explants were maintained on Millipore filter platforms up to 44 days and on sponge foam matrices up to 86 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The previously established medulloblastoma cell line D283 Med (Friedman et al, 1985) and primary explants of five medulloblastomas derived from patients ranging in age from ten months to I6 years were cultured on a Gelfoam matrix system which has been shown to favour differentiation, as assessed morphologically, in a variety of human and experimental gliomas (Rubinstein et al, 1973;Rubinstein & Herman, 1975;Sipe et al, 1974;Vraa-Jensen et al;1976). Antigenic expression of the neuron-associated class III [3-tubulin, MAP2, tau protein, and synaptophysin demonstrate the neuroblastic phenotype of the medulloblastoma cultures and all were found to be highly variable and focal in Gelfoam cultures of the D283 Med line and in primary explants.…”
Section: Discussionmentioning
confidence: 99%
“…The previously established medulloblastoma cell line D283 Med (Friedman et al, 1985) and primary explants of five medulloblastomas derived from patients ranging in age from ten months to I6 years were cultured on a Gelfoam matrix system which has been shown to favour differentiation, as assessed morphologically, in a variety of human and experimental gliomas (Rubinstein et al, 1973;Rubinstein & Herman, 1975;Sipe et al, 1974;Vraa-Jensen et al;1976). Antigenic expression of the neuron-associated class III [3-tubulin, MAP2, tau protein, and synaptophysin demonstrate the neuroblastic phenotype of the medulloblastoma cultures and all were found to be highly variable and focal in Gelfoam cultures of the D283 Med line and in primary explants.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of mixed ependymoma and neuronal tumor was considered, however, the immunohistochemical [3,7,8] and ultrastructural [9][10][11][12][13] studies confirmed the tumor to be an ependymoma.…”
Section: Discussionmentioning
confidence: 99%